Analysis of MSMEs Growth Post Pandemi Covid-19 in Medan - Sasmita, Riza; Batubara, Chuzaimah; Kamilah, Kamilah (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2022)
The purpose of this research is to determine the impact of the COVID-19 pandemic on small and medium-sized enterprises (SMEs) in the city of Medan, as well as solutions and measures to improve SMEs after the pandemic. This investigation employs a descriptive qualitative case study methodology. Documentary research, interviews, observations, and the distribution of questionnaires were used in this study to acquire data from Medan City MSME managers. The data analysis employed is a qualitative-interactive analysis comprised of three concurrent strands of activity: data reduction, data presentation, and conclusion. This study demonstrates the effects of COVID-19 on the development of small and medium-sized enterprises in Medan. In 2018, there were 1,664 MSMEs; in 2019, there will be 1,072. In 2019, the number of MSMEs in Medan City decreased by 594, or 34.5%, because COVID-19 affected all industries, including MSMEs. There were 1,040 MSMEs in 2020. This year, the number of small and medium-sized enterprises (SMEs) in Medan City decreased by 32, or 0.2%, due to the continued prevalence of the COVID-19 virus. There will be 1,179 SMEs in 2021. In 2021, the number of small and medium-sized enterprises will increase by 139, or 14.0%. Faced with the ongoing COVID-19 pandemic, small and medium-sized businesses (SMBs) in Medan City are innovating their product marketing, particularly through the use of digital marketing.